His and Hers, time and income: How intra-household dynamics impact nutrition in agricultural households - Twyman, Jennifer; Useche, Pilar; González, Carolina; Talsma, Elise F.; Lopera, Diana Carolina (International Center for Tropical Agriculture, 2018)
Understand how dietary diversity is impacted by intra-household decision making processes related to income, nutrition information and time allocation (with primary focus on principle men and women in the household). In particular, we will examine how nutrition information, income, and time allocation impact food consumption. Furthermore, we will analyze whether households where women have more decision-making power, as measured by choice experiments, systematically differ in their actual consumption patterns from households where men’s preferences are more highly represented in decision-making. We will use two types of data collection instruments: Surveys (Household and individual level) Hypothetical and real choice experiments